Glutathione Peroxidase-1 Suppresses the Unfolded Protein Response upon Cigarette Smoke Exposure. (13th December 2016) - Geraghty, Patrick; Baumlin, Nathalie; Salathe, Matthias A.; Foronjy, Robert F.; D'Armiento, Jeanine M.
Abstract : Oxidative stress provokes endoplasmic reticulum (ER) stress-induced unfolded protein response (UPR) in the lungs of chronic obstructive pulmonary (COPD) subjects. The antioxidant, glutathione peroxidase-1 (GPx-1), counters oxidative stress induced by cigarette smoke exposure. Here, we investigate whether GPx-1 expression deters the UPR following exposure to cigarette smoke. Expression of ER stress markers was investigated in fully differentiated normal human bronchial epithelial (NHBE) cells isolated from nonsmoking, smoking, and COPD donors and redifferentiated at the air liquid interface. NHBE cells from COPD donors expressed heightened ATF4, XBP1, GRP78, GRP94, EDEM1, and CHOP compared to cells from nonsmoking donors. These changes coincided with reduced GPx-1 expression. Reintroduction of GPx-1 into NHBE cells isolated from COPD donors reduced the UPR. To determine whether the loss of GPx-1 expression has a direct impact on these ER stress markers during smoke exposure, Gpx - 1 −/− mice were exposed to cigarette smoke for 1 year. Loss of Gpx - 1 expression enhanced cigarette smoke-induced ER stress and apoptosis. Equally, induction of ER stress with tunicamycin enhanced antioxidant expression in mouse precision-cut lung slices. Smoke inhalation also exacerbated the UPR response during respiratory syncytial virus infection. Therefore, ER stress may be an antioxidant-related pathophysiological event in COPD.